Pengembangan LKS Berbasis Model Inquiry Terbimbing Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Himsar Himsar (Institut Agama Islam Negeri Padangsidimpuan, 2025)
This research effort is through the development of LKS (Student Worksheet) guided inquiry model, the process of the emergence of this LKS is starting from the problem in the field of the use of LKS that are not in accordance with the analysis of student needs, not in accordance with the school environment, the LKS presented is instant from the publisher. The solution for LKS like this is the development of LKS based on the guided inquiry model that guides students to the problem, the problem is analyzed, and solutions are sought to solve it. This research method uses Development, the development used according to Thiagarajan's opinion (Trianto 2009) the stages are defining (define), designing (design), developing (development), and disseminating (disseminate). The Definition stage is carried out in the form of curriculum analysis, material analysis, Student Character. At this stage, the adjustment of Student competencies to their needs for material and environment. The design phase focuses on creating tests based on the criteria of the guided inquiry model. The constructed criteria-referenced tests become worksheet instruments. These tests are validated by a validator until they are valid. The worksheets then contain the validated tests. Worksheets that contain valid tests and align with the steps of the guided inquiry model are validated by validators and practitioners. The development phase is when the worksheets have received valid scores from validators and practitioners related to the worksheets containing the tests. The final phase, dissemination, involves testing the worksheets in samples or other classes.